Cyclic-di-GMP Induces STING-Dependent ILC2 to ILC1 Shift During Innate Type 2 Lung Inflammation - Cavagnero, Kellen J.; Badrani, Jana H.; Naji, Luay H.; Amadeo, Michael B.; Leng, Anthea S.; Lacasa, Lee Diego; Strohm, Allyssa N.; Renusch, Samantha R.; Gasparian, Suzanna S.; Doherty, Taylor A. (Frontiers in Immunology, 2021)
Type 2 inflammation is found in most forms of asthma, which may co-exist with recurrent viral infections, bacterial colonization, and host cell death. These processes drive the accumulation of intracellular cyclic-di-nucleotides such as cyclic-di-GMP (CDG). Group 2 innate lymphoid cells (ILC2s) are critical drivers of type 2 lung inflammation during fungal allergen exposure in mice; however, it is unclear how CDG regulates lung ILC responses during lung inflammation. Here, we show that intranasal CDG induced early airway type 1 interferon (IFN) production and dramatically suppressed CD127+ST2+ ILC2s and type 2 lung inflammation during Alternaria and IL-33 exposure. Further, CD127−ST2−Thy1.2+ lung ILCs, which showed a transcriptomic signature consistent with ILC1s, were expanded and activated by CDG combined with either Alternaria or IL-33. CDG-mediated suppression of type 2 inflammation occurred independent of IL-18R, IL-12, and STAT6 but required the stimulator of interferon genes (STING) and type 1 IFN signaling. Thus, CDG potently suppresses ILC2-driven lung inflammation and promotes ILC1 responses. These results suggest potential therapeutic modulation of STING to suppress type 2 inflammation and/or increase anti-viral responses during respiratory infections.